ENDEMIC GOITER WITH THE DISEASE TERRITORIES ACCORDING TO SPREAD (World Bulletin of Public Health, 2025)
In the general population, nodular goiter is detected in 3-5% of patients during palpation of the thyroid gland, and in 20-35% during screening ultrasound (US) and tissue autopsy. There are many etiological factors for the development of nodular non-toxic goiter (goitrogens, according to epidemiological studies conducted by the Federal Endocrinological Sciences center, there are no regions in the Russian Federation where the population is not at risk of developing iodine deficiency diseases.
Keywords: screening; Endocrinological; deficiency